Universal social protection: A target for all - Mariana Balboni; Aline Peres (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
Social protection has gained relevance and garnered increasing interest over recent decades. Developing countries are progressively adopting more programmes and policies to protect their poor and vulnerable populations, while international organisations and donors work to enhance the capacity of States to develop efficient and sustainable systems. Social protection schemes also play a key role in stabilizing economies, protecting livings standards and providing social security for all.
Keywords: 330; Universal; social; protection; target; all